Performance of EU Countries in Managing Electrical and Electronic Equipment Waste in the Context of the Circular Economy - Catalina Soriana Sitnikov; Laura Vasilescu; Anca Bandoi; Daniela Firoiu; Sorin Tudor; Lili tenea (Amfiteatru Economic, 2023)
In today's context, the circular economy is a model of sustainable economic development that is becoming particularly important for the electrical and electronic waste (e-waste) industry. From this perspective, the research in the article will be carried out for the 27 European Union Member States regarding the performance in managing electrical and electronic waste, also highlighting the changes that have occurred within the analyzed countries in the years 2015 and 2020. The empirical study will adopt a complex econometric tool, represented by hierarchical cluster analysis, with countries grouped into four clusters over two distinct periods (2015 and 2020) where the variables included will be the following: the amount of e-waste generated per capita, the amount of electrical and electronic equipment sold on the market per capita, electrical and electronic waste recycled and prepared for reuse, and the circularity rate. Based on these variables, the article will analyze the performance in e-waste management (gain or loss of performance) in the analyzed years, underlying also the capacity of analyzed countries to adapt to the new demands imposed by the circular economy on the coordinates of sustainable development. In addition, theoretical, methodological, and empirical implications will be presented, which, through their implementation, can influence the managerial and environmental policy decisions.
Keywords: E61; E70; F64; Q43; G53; 330; circular economy; e-waste; sustainable development; hierarchical clusters; European Union